Dyselectrolemia in patients with dengue fever in tertiary care hospital - Verma, Shubhangi Hirasingh; Jagtap, Pranjal Prakash (International Journal of Advances in Medicine, 2021)
Background: Dengue is a mosquito borne acute febrile illness caused by viruses belonging to group flaviviridea. Primarily this disease is transmitted by Aedes aegypti and Aedes albopictus. There are 4 serotypes of dengue virus i.e. DENV 1, 2, 3, and 4. According to World Health Organization (WHO) report in 2009, globally around 2.5 billion people live in dengue endemic areas and more than 50 million people are infected with dengue fever annually. Dyselectrolemia is very common among dengue patients. Many studies found that hyponatremia is common in Dengue, DHF and especially in dengue shock patients. The purpose of this study was to evaluate serum sodium as the predictor of prognosis in dengue fever. Methods: Present study was longitudinal in nature conducted on 100 dengue patients. All patients fulfilling inclusion criteria and exclusion criteria were taken up for the study. Study was carried from August to October 2020. Serum electrolyte kit was used to analyze electrolytes. Results: Majority (39%) of the dengue patients was in the age group of 18-35 years and most of them were male. Fever was the most common complaint, present in all (100%) the patients followed by myalgia (96%), headache (89%), retro-orbital pain (88%), rash (73%) and joint pain (71%). Hyponatremia was the chief electrolyte abnormality, present among 61% dengue patients and it was associated with poor prognosis. Conclusions: We have found that hyponatremia was the chief electrolyte abnormality among dengue patients and prognosis was inversely related to hyponatremia.